Pelatihan Kemampuan Mendongeng kepada Guru-Guru PAUD dan TK Makanatut Thalibin Desa Pulantan Kecamatan Aluh-Aluh - Jamiatul Hamidah; Sri Normuliati; Istiqamah Istiqamah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
This community service aims to improve the knowledge and skills of storytelling for teachers and parents of PAUD students in Pulantan Village, Aluh-Aluh sub-district. This dedication was held on Thursday, March 22, 2018, in PAUD Makanatut Talibin. The target of this activity is PAUD teachers and student parents/guardians. The reason for choosing this school is because the schools are classified as far from the city center and include the villages built by the PKH program. The method used in the implementation is by presentation/lecture and storytelling simulation/training. After this activity was carried out, it was concluded that storytelling had not become a habit and approach to the formation of children's character both by teachers and parents. This is because teachers and parents have very little ability in storytelling. Therefore, in the future, it is hoped that further training will be carried out by involving more teachers and parents and bringing in speakers who are more competent in storytelling such as Mother Enik Mintarsih, a storyteller from South Kalimantan.